2018
DOI: 10.1126/science.aah6499
|View full text |Cite
|
Sign up to set email alerts
|

The epigenetic control of stemness in CD8 + T cell fate commitment

Abstract: After priming, naïve CD8 T lymphocytes establish specific heritable transcription programs that define progression to long-lasting memory cells or to short-lived effector cells. Although lineage specification is critical for protection, it remains unclear how chromatin dynamics contributes to the control of gene expression programs. We explored the role of gene silencing by the histone methyltransferase Suv39h1. In murine CD8 T cells activated after infection, Suv39h1-dependent trimethylation of histone H3 lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
207
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(220 citation statements)
references
References 42 publications
13
207
0
Order By: Relevance
“…22 The acquisition of effector and memory T cell functions requires not only that genes involved in lineage commitment are turned on but also that genes maintaining stemness are repressed. [23][24][25][26] Consequently, DNA methylation as well as DNA demethylation and histone modifications conferring gene activation as well as repression are required for T cells to differentiate. 27 Equally important, the epigenetic code can act as the memory of cellular identity because it can be transmitted from one cell generation to the next, 28 obviously crucial for memory T cells that exhibit chromatin accessibility maps similar to effector T cells years after the inciting infection has been cleared.…”
Section: Epigenetic Studies In T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The acquisition of effector and memory T cell functions requires not only that genes involved in lineage commitment are turned on but also that genes maintaining stemness are repressed. [23][24][25][26] Consequently, DNA methylation as well as DNA demethylation and histone modifications conferring gene activation as well as repression are required for T cells to differentiate. 27 Equally important, the epigenetic code can act as the memory of cellular identity because it can be transmitted from one cell generation to the next, 28 obviously crucial for memory T cells that exhibit chromatin accessibility maps similar to effector T cells years after the inciting infection has been cleared.…”
Section: Epigenetic Studies In T Cellsmentioning
confidence: 99%
“…Epigenetic changes occur with T cell activation and differentiation . The acquisition of effector and memory T cell functions requires not only that genes involved in lineage commitment are turned on but also that genes maintaining stemness are repressed . Consequently, DNA methylation as well as DNA demethylation and histone modifications conferring gene activation as well as repression are required for T cells to differentiate .…”
Section: Introductionmentioning
confidence: 99%
“…T cell differentiation is intimately linked to epigenetic programming, but the mechanistic role of epigenetic marks in steering T cell differentiation 40,60,61,63,69,70 and thymic selection [71][72][73][74][75] has only recently become more clear. Here we observed that ablation of Dot1L in the T cell lineage differentially affected CD4 + and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Such observations have also been reported for specialized cases of terminal differentiation. For instance, a defect of the H3K9 trimethylase Suv39h1 maintains the re-programming capacity of CD8 + lymphocytes [13] and chromatin acetylation induces the developmental plasticity of oligodendrocyte precursors [14]. Long before these studies, it had already been shown that cellular differentiation is associated to an overall loss of DNA accessibility, measured experimentally with DNAseI [15].…”
Section: Introductionmentioning
confidence: 99%